Respuestas

  • Usuario de Brainly
2013-06-17T22:32:15+02:00
2x - 6 = 3x - 36 + x
2x - 3x -x = - 36+ 6
 - 2x = - 30
x = - 30/ - 2
x = 15

7x - 12 - 12x = - x + 12
7x - 12x +x = 12 + 12
- 4x = 24
x = 24 / -4
x = - 6

- 14+ 3x = 4x + 21 +4x
3x - 4x - 4x = 21 + 14
- 5x = 35
x = 35 / -5
x = - 7

- 8x - 10 + 2x = 5x + 3x + 6
- 8x + 2x - 5x - 3x = 6 + 10
- 14x = 16
x = 16 / - 14
x = - 8/7

x - 8x - 4 + 7 = 18 + 3x + 5
- 4 + 7 - 18 - 5 = 3x -x + 8x
     - 20 = 10x
- 20/10 = x
 - 2 = x

espero que te sirva, salu2!!!!!